2016
DOI: 10.1017/jfm.2016.345
|View full text |Cite
|
Sign up to set email alerts
|

Modal energy flow analysis of a highly modulated wake behind a wall-mounted pyramid

Abstract: We experimentally investigate the highly modulated turbulent wake behind a wall-mounted square-base pyramid protruding through the boundary layer. We present the first modal energy flow analysis of a time-resolved three-dimensional velocity field from experimental particle image velocimetry data. The underlying low-order representation is optimized for resolving the base-flow variation as well as the first and second harmonics associated with vortex shedding – generalizing the triple decomposition of Reynolds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…This can be linked to the fact that both are evaluated in the vicinity of the fluctuations intensity peaks of particular wakes. A similar energy balance is also reported by Hosseini et al [15], who considered a flow past a wall-mounted pyramid, focusing at the area around shedding intensity peak. The authors show that the entire gain of the mean energy is due to the convection term, whereas the loss splits between the production term and the pressure term in the proportion of 30 % and 70 %.…”
Section: Energy Budgetsupporting
confidence: 79%
See 2 more Smart Citations
“…This can be linked to the fact that both are evaluated in the vicinity of the fluctuations intensity peaks of particular wakes. A similar energy balance is also reported by Hosseini et al [15], who considered a flow past a wall-mounted pyramid, focusing at the area around shedding intensity peak. The authors show that the entire gain of the mean energy is due to the convection term, whereas the loss splits between the production term and the pressure term in the proportion of 30 % and 70 %.…”
Section: Energy Budgetsupporting
confidence: 79%
“…40 % − 60 % and the former two account for further 20 % − 40 %. Hosseini et al [15] reported a similar tendency in the flow past a pyramid. The energy balance of its first shedding harmonic was driven entirely by the production term, while losses were caused by the convection term (20 %) and the stochastic fluctuations production (70 %, referred to as residual in Hosseini et al [15]).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…In particular, there is abundant literature using Singular Value Decomposition (SVD) based methods such as POD/PCA (Taira et al, 2017), DMD (Schmid, 2010;Kutz et al, 2015;, SPOD (Sieber et al, 2015). These methods generally do not perform well in cases with any kind of traveling wave behavior (Taira et al, 2017;Riches et al, 2018;Hosseini et al, 2016). The reason for this lies in the creation of fixed spatial functions/basis functions.…”
Section: So How Are These Variations Treated?mentioning
confidence: 99%
“…The concept of transfer learning exploits the fact that once a model has been trained for one task, it can be easily remolded to complete similar tasks (Brownlee, 2017). In practice this means that a neural network can be trained for a specific computer vision task and then easily be reused; i.e., a network originally trained for classifying breeds of dogs within photographs can be easily reused on aerodynamics data (the FASTAI project has a lecture series expanding at length on this theme; Howard et al, 2019). This may seem like an exotic claim but there is solid reasoning underpinning the claim.…”
Section: Introductionmentioning
confidence: 99%